EVALUATION OF AGRICULTURAL SUBSIDY POLICIES AND THEIR IMPACT ON FARMERS’ WELFARE - Manaf, Sulhan (Penelitian dan Pengembangan Ilmu, 2025)
Agricultural subsidies play an important role in improving the welfare of small farmers in developing countries, but their effectiveness is still debated. This research aims to evaluate the impact of subsidy policies on the economic welfare of small farmers, considering the challenges faced by this group in the context of market uncertainty and climate risk. This research aims to measure the effectiveness of agricultural subsidy policies in increasing income, productivity and access to resources for small farmers in developing countries. The approach used is Systematic Literature Review (SLR), with data collection from the Scopus and Web of Science databases. Analysis was carried out using manual coding techniques and NVivo software to identify main themes from 36 relevant studies. The findings show that input subsidies, price subsidies, credit assistance subsidies significantly increase the productivity and income of small farmers, despite the risk of dependency and market distortion. The quality of governance and technology adoption moderate the positive impact of subsidies. This research highlights the importance of context-based and participatory subsidy policy design to maximize benefits for small farmers, and contributes to the development of theory and practice in agricultural policy.